Development of inclusion complex based on cyclodextrin and oxazolidine derivative - Rafael Ramos Silva; Cézar Augusto da Cruz Amorim; Maria do Carmo Alves Lima; Marcelo Montenegro Rabello; Marcelo Zaldini Hernandes; Moacyr Jesus Barreto de Melo Rêgo; Maira Galdino da Rocha Pitta; Maria Danielly Lima de Oliveira; César Augusto Souza de Andrade (Universidade de São Paulo, 2023)
Abstract Oxazolidine derivatives (OxD) have been described as third-line antibiotics and antitumoral agents. The inclusion complexes based on cyclodextrin could improve the solubility and bioavailability of these compounds. A novel synthetic OxD was used, and its inclusion complexes were based on 2-hydroxy-beta-cyclodextrin (2-HPβCD). We conducted an in silico study to evaluate the interaction capacity between OxD and 2-HPβCD. Characterization studies were performed through scanning electron microscopy (SEM), Fourier-transformed infrared (FTIR), nuclear magnetic resonance spectroscopy (1H-NMR), X-ray diffraction (XRD), and thermal analyses. A kinetic study of the OxD was performed, including a cytotoxicity assay using peripheral blood mononuclear cells (PBMCs). The maximum increment of solubility was obtained at 70 mM OxD using 400 mM 2-HPβCD. SEM analyses and FTIR spectra indicated the formation of inclusion complexes. 1H-NMR presented chemical shifts that indicated 1:1 stoichiometry. Different thermal behaviors were obtained. The pharmacokinetic profile showed a short release time. Pure OxD and its inclusion complex did not exhibit cytotoxicity in PBMCs. In silico studies provided a foremost insight into the interactions between OxD and 2-HPβCD, including a higher solubility in water and an average releasing profile without toxicity in normal cells.